Impact of integrated upper limb spasticity management including botulinum toxin A on patient-centred goal attainment: rationale and protocol for an international prospective, longitudinal cohort study (ULIS-III). Issue 6 (17th June 2016) - Turner-Stokes, Lynne; Ashford, Stephen; Jacinto, Jorge; Maisonobe, Pascal; Balcaitiene, Jovita; Fheodoroff, Klemens
Abstract : Objectives: Describe the rationale and protocol for the Upper Limb International Spasticity (ULIS)-III study, which aims to evaluate the impact of integrated spasticity management, involving multiple botulinum toxin A (BoNT-A) injection cycles and concomitant therapies, on patient-centred goal attainment. Outline novel outcome assessment methods for ULIS-III and report initial evaluation data from goal setting in early stages of the study. Design: Large international longitudinal cohort study of integrated upper limb spasticity management, including BoNT-A. Participants and setting: ULIS-III is a 2-year study expected to enrol >1000 participants at 58 study centres across 14 countries. Interventions: The study design is non-interventional and intended to reflect real-life clinical practice. It will describe injection practices and additional treatment strategies, and record clinical decision-making in a serial approach to long-term spasticity management. Outcome measures: ULIS-III will use a goal-directed approach to selection of targeted standardised measures to capture the diversity of presentation, goals and outcomes. ULIS-III will implement the Upper Limb Spasticity Index, a battery of assessments including a structured approach to goal attainment scaling (Goal Attainment Scaling—Evaluation of Outcomes for Upper Limb Spasticity tool), alongside a limited set of standardised measures, chosen according to patients' selected goal areas. Concomitant therapy inputs, patient satisfaction with engagement in goal setting, health economic end points and health-related quality of life data will also be captured. Results of initial evaluation of goal quality: Recruitment started in January 2015. By June 2015, 58 sites had been identified and initial data collected for 79 patients across 13 sites in 3 countries. Goal setting data were quality-checked and centres rated on the basis of function-related and Specific, Measurable, Achievable, Realistic, Timed (SMART) characteristics of goal statements. Overall, 11/13 centres achieved the highest rating (A++). Conclusions: ULIS-III will provide valuable information regarding treatment of and outcomes from real-life upper limb spasticity management worldwide. Trial registration number: NCT02454803; Pre-results.